Gambaran Kepatuhan Masyarakat terhadap Protokol Kesehatan dalam Pencegahan COVID-19 di Wilayah Kerja Puskesmas Kabanjahe - Sitanggang, Tiur Maria Carolina BR; Sitanggang, Ervina Julien; Sibarani, Joseph; Ompusunggu, Henny Erina Saurmauli (Nommensen Journal of Medicine, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which causes symptoms of shortness of breath, fever, and cough and is contagious and has infected tens of millions of people worldwide. One of the factors that can lead to the transmission of COVID-19 is the community's non-obedience with the health protocols set by the government, namely 3M.Objective: This study aims to determine the description of community obedience in the working area of the Kabanjahe Public Health Center to health protocols in preventing COVID-19.Methods: This study is a descriptive study with a cross-sectional design. There are 162 respondents who were selected by simple random sampling technique. The research sample was from the population in the working area of the Kabanjahe Public Health Center who were willing to be interviewed. Data were taken using a questionnaire.Results: The results showed that the majority of people in the working area of the Kabanjahe Public Health Center always wash their hands with soap and running water for 40-60 seconds (40,7%) and always use alcohol-based antiseptic liquid (handsanitizer) for at least 20-30 seconds if there is no running water (35,2%), always avoid touching eyes, nose and mouth with unclean hands (50,6%). Always use a mask if you have to leave the house (74,7%) and always use a mask by covering the nose and mouth until the chin reaches (69,8%). Always maintain a minimum distance of 1 meter from other people when outside the house (48,8%) and always avoid crowded places and crowds (55,6%), always take a shower and change clothes after traveling (61,7%), always exercising regularly for at least 30 minutes a day (43,8%), and always getting enough rest for at least 7 hours (67,9%).Conclusion: The majority of the people in the working area of the Kabanjahe Health Center are carrying out health protocols in preventing COVID-19.